AB0138 CHARACTERIZATION OF SERUM CYTOKINE PROFILE IN PATIENTS WITH ACTIVE LUPUS NEPHRITIS - Rahme, Z.; Gatto, M.; Ghirardello, A.; Cruciani, C.; Pettorossi, F.; Zaramella, A.; Franco, C.; Doria, A. (Annals of the rheumatic diseases, 2023)
Cytokines (CKs) are known to play a role in the pathogenesis of lupus nephritis (LN), yet their role as biomarkers is still debated. To describe the CKs picture in patients with active LN and to assess possible clinical correlates in LN course. A prospective cohort study including patients with active biopsy-proven LN was performed. Serum CKs were assessed at the time of diagnosis and at 3 subsequent time points (3, 6 and 12 months) during follow-up. Clinical and serological data were collected for further analysis. BLyS (B Lymphocyte stimulator) and interleukin (IL)-37 were measured by ELISA assays (Quantikine BAFF, R&D, USA, detection limit DL 0.02 ng/mL; IL37 ELISA kit, Adipogen, Swizerland, DL 0.001 ng/mL), IL-2, IL-10, IL-17A and IL-18 (pg/mL) by Luminex multiplex assay (Millipore, USA, DL 0.6 pg/mL for all), according to the manufacturers' instructions. Measurements for IL-37 and BLyS were matched with sera of sex- and age- matched healthy subjects (HC). Mann-Whitney test was used for comparisons between two independent groups, Wilcoxon log-rank test for paired comparisons at different time points, Spearman's correlation coefficient for associations between CK and between CK and clinical features. Twenty-seven patients with active LN (mean±SD age 41.75±14.74, 78.8% women) were included for initial CK analysis at the time of LN activity. At baseline (T0), BLyS levels were significantly increased in LN compared with HC (median [range], 1.107 [0.326-4.00] vs. 0.563 [0.265-1.409]; p<0.0001); IL-37 was significantly reduced in LN compared with HC (median [range] 0.016 [0.001-0.251] vs. 0.056 [0.001-1.147]; p = 0.0185). At T0, median (range) levels of IL-2, IL-10, IL-17A and IL-18 were: IL-2 0.640 (0-37.82), IL-10 2.60 (0-106.86), IL-17A 2.10 (0-138.20), IL-18 243.10 (28.20-950.30). The longitudinal association study between CK levels of the entire cohort revealed a trend of inverse correlation between IL-37 and BLyS (r=-0.281, p=0.06) and a direct correlation between BLyS and IL-18 (r=0.330, p=0.04) and between IL-2 and IL-17A (r=0.470, p<0.001) (Figure 1). A subset of 17 patients (70.6% F, mean age at renal flare 34.3±18.6y, mean duration of disease at the time of renal flare 4.99±8.94y, caucasian ethnicity n=14, 82.3%), was followed-up prospectively: 7 (41.18%) had biopsy-proven (III-IV class) proliferative glomerulonephritis. Proteinuria at T0 was 2.19±1.35 g/24h. All patients were treated with pulsed glucocorticoids (GCS, 750-2500 mg) followed by oral GCS (0.3-0.5mg/kg/day prednisone equivalent) and immunosuppression1. Higher titres of IL-18 were present in the sera of patients with proliferative forms of LN (p=0.053) and with a higher SLEDAI-2K score at T0 (p=0.0759). A significant correlation was found between IL-2, and to a lesser extent of IL-17, with anti-dsDNA antibodies (IL2: r=0.6098, p=0.0094; IL17: r=0.4591, p=0.0638). High levels of IL-17 correlated with lower C3 at T0 (r=-0.5085, p=0.0372). No significant longitudinal changes in CKs levels nor correlation with clinical features were observed. Patients with proliferative LN and higher SLEDAI-2K scores displayed higher levels of IL-18, thus supporting IL-18 likely role in the pathogenesis of LN. We documented a correlation between IL2 and higher titres of anti-dsDNA antibodies and an inverse correlation between IL-17 and C3 at baseline, suggesting a contribution of CKs to LN onset. Our study was limited by the small sample size, limiting retrieval of significant data on CK levels and clinical-laboratoristic changes at different time points, demanding further studies. [1]Fanouriakis A, et al 2019 Ann Rheum Dis 2019;78:736-745 [2]Mende, et al. Front Immunol vol. 9 1250. 7 Jun. 2018, doi:10.3389/fimmu.2018.01250 NIL. None Declared. [Display omitted]